Otimização da síntese etanólica do biodiesel de pinhão manso (Jatropha curcas L.) e determinação de seus parâmetros fluidodinâmicos - Freire, Lécia Maria da Silva (2009)
The most applied process for biodiesel production is the transesterification reaction based on alkaline catalysts, due to their faster kinetics and appreciable conversion rate. Then, low cost catalysts (alkaline, alkaline earth and transition metal hydroxides), are often used. In such context, the present work aims to evaluate the catalytic activity of alkaline hydroxides (NaOH and KOH) on Jatropha curcas L. ethyl biodiesel synthesis. Thus, the Jatropha curcas L. seeds were dried at 105 oC for 2 hours, in order to removing volatile compounds and disrupting the vegetal cells membranes improving oil releasing. The mechanical oil extraction yielded 38% of efficiency, whereas the chemical extraction resulted in 42% yielding . Chromatographic data showed that oleic (18:1) and linoleic (18:2) acids were the main components of Jatropha curcas oil (35.89% and 44.4% respectively). Hence, the transesterification reactions were carried out using ethoxide ions previously stored at 6 oC, for 12 and 24 hours, and their yielded biodiesels has presented the following composition: B12KOH - 89.8%, B24KOH - 98.1%, B12NaOH - 86.7% and B24NaOH - 99.3%. Thus, it can be inferred that the oil transesterification is widely affected by the hydroxyl (hydrolysis) and ethoxyl ions. Furthermore, for all samples, the uid dynamic properties were appropriated for their commercialization.